103 Defining the lupus-associated pulmonary hypertension phenotype. (April 2019) - Mizus, Marisa; Li, Jessica; Goldman, Daniel; Petri, Michelle
Abstract : Background: Pulmonary hypertension (PH) is a major cause of death in systemic lupus erythematosus (SLE). Case reports and case series have identified hypocomplementemia and autoantibodies, including antiphospholipid and anti-RNP, in SLE patients with PH. This is the first study to define the lupus phenotype associated with pulmonary hypertension (PH) using multiple autoantibodies. Methods: 207 (8%) SLE patients with PH, defined as a right ventricular systolic pressure greater than 40 mmHg on transthoracic echocardiogram or as pulmonary artery dilatation noted on computed tomography of the chest, were identified from the Hopkins Lupus Cohort (94% female, 56.5% African American, 39% Caucasian, mean age 45.6 years). Agglomerative hierarchical clustering algorithm with Wards method was used to cluster the patients who had PH, based on their history of autoantibodies. Autoantibodies used in the clustering analysis included lupus anticoagulant, anticardiolipin, anti-beta2 glycoprotein I, antidsDNA, antiSm, antiRNP, false positive (FP)RPR, antiRo, antiLa, and hypocomplementemia (C3 ever low or C4 ever low). All analyses were performed in JMP version 13.0 and R version 3.5.1 using packages cluster and gplots. Results: There were five unique clusters. Clusters 1 and 2 had high frequencies of hypocomplementemia, antiphospholipid antibodies, and anti-dsDNA. Cluster 2 additionally had a high frequency of FP-RPR. Cluster 3 had high frequencies of hypocomplementemia, anticardiolipin, anti-Sm, anti-RNP, and anti-dsDNA. Cluster 4 had high frequencies of hypocomplementemia, anti-Ro, anti-La, and anti-dsDNA. Cluster 5 had only moderate frequencies of anti-dsDNA and anti-cardiolipin antibody. Two clusters were defined by antiphospholipid antibodies. Two clusters were defined by anti-RNP and anti-Sm. Multiple clusters had elevated anti-dsDNA and hypocomplementemia. Conclusions: PH in SLE is defined by five unique autoantibody clusters. Antiphospholipid and anti-RNP/Sm clusters clearly separate, which likely indicates different pathophysiologic mechanisms. Four of the five clusters have anti-dsDNA and low complement components. Our next step is to exploreboth in the literature and within our cohortthe natural history and response to treatment of these clusters. Funding Source(s): NIH Grant R01-AR069572 Clustering of Autoantibodies in Lupus-Associated Pulmonary Hypertension